Changes HDL and LDL Levels After Using Olive Oil and Figs Extract on White Rats with A High-Fat Diet - Alhumaerah, Musdalifah; Syamsu, Rachmat Faisal; Karim, Marzelina; Nurmadilla, Nesyana; Murfat, Zulfitriani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Hypercholesterolemia often initiates the pathogenesis of atherosclerosis which can occur slowly. As free radicals increase, the need for antioxidants also increases. Reducing LDL and increasing HDL levels is the target of therapy for hyperlipidemia patients with the main goals of lifestyle changes and drug therapy. Olive oil and fig extract have therapeutic benefits as alternative treatments from MUFA content dominated by oleic acid and phenolic compounds. The polyphenol content is known to inhibit the formation of atherosclerosis and inhibit the increase in MCP-1 levels in white mice on a high-fat diet. Therefore, it is hoped that the administration of figs extract and olive oil can overcome dyslipidemia, especially changes in HDL and LDL levels in white mice. To determine changes in HDL and LDL levels. The research conducted was a true experimental research was used with a Pre-Post control group research design and test statistical analysis with Microsoft Office 2013. Showed there was an effect of fig extract (Ficus Carica L) on changes in HDL levels and the effect of olive oil (Olea europea L) on changes in LDL levels in white rats (Rattus novergicus) fed a high-fat diet. The intervention of fig extract and olive oil had a significant effect on the group given the single intervention.